EVALUASI PELAYANAN PERUSAHAAN DAERAH AIR MINUM (PDAM) BENGKALIS KABUPATEN BENGKALIS - Juliana, Septa (UIR PRESS, 2018)
This study aims to find out the service of Bengkalis PDAM Bengkalis Regency and to know the obstacles and service solutions Bengkalis District of Bengkalis. Data analysis in this research is by using quantitative method with descriptive analysis technique that describes and summarizes as condition of variable situation that exist in this research object. Based on the data discussed in the previous chapter, Bengkalis PDAM Service Evaluation uses tangible indicators, reliability, responsiveness, assurance, and empathy (empathy) can be seen that the services provided has been running well, it's just in terms of empathy (empathy) customers feel the PDAM is not concerned with the service expected by the customer, because there is still complaints from customers about the clean water service provided is about the quality of the water. Meanwhile, things that can hamper the service of PDAM include: 1) Season factor, in this case in the dry season. At that time PDAM is very difficult to find water source. 2) PDAM water pipe factor that is old, old pipe can reduce water quality. 3) Factors from outside the organization, in this case PLN also affect the service, PLN will impede the service if the power goes out. 4) Factor of the customer, if there are customers who are delinquent the payment of water.